Study on Rule of Heavy Metal Cu2+ in Small and Medium-Sized Tailings Ponds under Rainfall-Evaporation-Transpiration Coupling. Issue 1 (February 2021) - Chen, Hongdan; Hao, Zhe; Zhang, Ying; Teng, Da; Wang, Xiaoming; Zhang, Qian
Abstract: In order to research the heavy metal migration rule of small and medium-sized tailings ponds under the action of climate, vegetation and groundwater, this paper consider the rainfall-evaporation-transpiration and coupling effect of groundwater, establish the model of different dam height, slope ratio, permeability coefficient and migration time impact on the migration of heavy metals of tailings dam, applied to Geostudio software, based on the orthogonal design method of factors significant difference analysis and design method of the comprehensive factors analysis, make up the simulation of the tailings heavy metal pollutants concentration of Cu2+ migration law. The results show that the height of tailing dam is inversely proportional to the average migration velocity of pollutant Cu2+. The effect of slope ratio on migration concentration of Cu2+ pollutant in tailings pond is not significant. The permeability coefficient has a highly significant influence on the migration of heavy metal Cu2+. At the same depth of tailings pond, when Cu2+ migrated for 365 days, the permeability coefficient increased with the increase of pollutant Cu2+ concentration. The concentration of heavy metal increased with the increase of migration time.